PAEDIATRIC ADRENOCORTICAL CARCINOMA: A CASE REPORT - Amir, Muhammad Salman; Muahammad Ali; Rehman, Adnan; Ghayyour, Fahad; Malik, Ihtisham; Khattak, Tahir Ghaffar (Journal of Postgraduate Medical Institute, 2023)
Adrenocortical carcinoma (ACC) is a relatively rare but an aggressive neoplasm that can have variety of manifestations. It can manifest in the form of virilization, hyperaldosteronism, cushingoid features or combination of that. Due to rapid appearance of signs and symptoms in children, these tumours can be diagnosed early however if delayed can bear worse prognosis as they tend to metastasize early in course of disease progression. We report a case of 4 years old female patient from Chitral, Pakistan who was referred to Endocrinology Department from Paediatric Department of Hayatabad Medical Complex, Peshawar Patient presented at paediatric OPD with complaints of weight gain, hirsutism, rashes over the face and acne. Patient had typical moon facies, buffalo hump and distended abdomen without striae as well as mass in the left hypochondrium on examination. On further evaluation clitoromegaly and pubic hair tanner stage 4 were found. Both Ultrasound and CT-Scan showed left supra-renal soft tissue mass invading the inferior venacava (IVC). She was further evaluated and her overnight dexamethasone suppression test (ODST) and serum testosterone levels were high although serum sodium and potassium were normal ruling out hyperaldosteronism. Next, biopsy was performed which was consistent with adrenocortical carcinoma. ACC although rare is highly aggressive tumor that requires early detection and diagnosis specially in children. If diagnosis is delayed prognosis may not be favourable. It therefore requires avid clinical suspicion to proceed onto diagnostic lines for patient’s benefit as well as physician’s satisfaction.